Lange practice tests : - Goldberg, Joel S. (McGraw-Hill Medical Publishing Division, 2006)
This book was designed to be an up-to-date mirror of the USMLE Step 3 examination. The content and questions types are designed around the current USMLE guidelines. Offering 15 comprehensive practice tests with a total of more than 750 review questions, this is the perfect study tool to assist time-strapped residences get through the study process.